Sistem Pendidikan Islam dalam Kerangka Nasionalis-Religius Berbasis Rahmatan lil 'alamin - Jaenuri Jaenuri (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2019)
Islam can be accepted by the Indonesian people in a relatively short time, because it is in accordance with the sociological style of diversity that has taken root in Indonesia. The process of Islamization in Indonesia also involves several components, such as traders, clerics, kingdoms, and Islamic educational institutions, which allow for even distribution to various segments of society. Islam is like giving a new alternative to lasting coral feudalism by offering equality of dignity, dignity, and upholding justice. The concept of education which undermines religious and nationalist values ​​is considered important because the reality is often found in the dichotomous separation between them. Whereas Islamic education carries the mission of rahmatalil alamin, in the midst of the current Islamophobia as a religion that is imaged closed and radical. The purpose of this paper is to get the concept of mengani Islamic education system within the framework of nationalism-religious based rahmatan lil alamin. Study by proposing a correlation of arguments and arguments, between the education system and the Qur'anic verses and relevant hadiths. As a result, a religious nationalist-based educational framework has a strong foundation of textual, psychological, historical and sociological Research.